2001
DOI: 10.1177/107110070102200415
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Recolonization During Foot Surgery: A Prospective Randomized Study of Toe Preparation Techniques

Abstract: Fifty patients undergoing foot or ankle surgery were randomized into two groups for the purposes of toe preparation. Twenty-four patients underwent a standard preparation which included placing antiseptic between the toes while 26 were additionally cleaned by sliding a gauze swab soaked in topical antiseptic back and forth several times. Povidone iodine followed by chlorhexidine in alcohol was used in both groups. All toes were covered by a sterile glove during surgery unless the toes themselves were to be ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 10 publications
1
30
0
2
Order By: Relevance
“…Other comorbidities associated with increased risk of postoperative infection include obesity, malnutrition, tobacco use, and immunosuppressive medication [11,21,43,45]. Another potential cause for greater concern for surgical site infections after foot and ankle surgery is the persistent colonization of the forefoot despite preoperative preparation [7,12,30,47,48,63,65]. Ostrander et al [47] reported positive cultures after application of surgical preparation solution in 125 patients, ranging from 23% to 98% from the hallux nailfold and second and third web spaces, compared with 10% to 35% from the anterior tibia control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other comorbidities associated with increased risk of postoperative infection include obesity, malnutrition, tobacco use, and immunosuppressive medication [11,21,43,45]. Another potential cause for greater concern for surgical site infections after foot and ankle surgery is the persistent colonization of the forefoot despite preoperative preparation [7,12,30,47,48,63,65]. Ostrander et al [47] reported positive cultures after application of surgical preparation solution in 125 patients, ranging from 23% to 98% from the hallux nailfold and second and third web spaces, compared with 10% to 35% from the anterior tibia control.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation to decrease infectious risk in foot and ankle surgery has been largely preoperative, including preoperative risk stratification [17,21,59,64] and evaluation of antiseptic skin preparations [7,12,30,47,48]. An additional measure taken by some foot and ankle surgeons is planned use of a brief course of prophylactic postoperative oral antibiotics after elective outpatient procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Los productos basados en yodo povidona se inactivan con la presencia de material orgánico. -La limpieza de la piel antes de la preparación antisépti-ca para cirugía fue más efectiva en reducir la carga bacteriana que la aplicación de antiséptico únicamente (21,29) Sin embargo, Lefebvre et al, realizaron una revisión y meta análisis (7 estudios con 1650 pacientes) con el fin de evaluar la ventaja de aplicar un lavado exhaustivo previo a la aplicación de la solución antiséptica con respecto al riesgo de ISO y no encontraron diferencias (RR. 1.02 IC 95% 0.82, 1.26).…”
Section: B En La Sala De Cirugíaunclassified
“…Finalmente, un metaanálisis que incluyó estudios con diferentes comparaciones para cirugía limpia identificó beneficio en el uso de solución alcohó-lica con clorhexidina al 0.5% comparado con una solución alcohólica de yodo povidona con un reducción del riesgo de infección del 53% (RR 0,47, IC95% 0,27-0,82 30 . Adicionalmente un estudio que comparó la diferencia entre clorhexidina+alcohol Vs yodo povidona+alcohol y el riesgo de infección del sitio quirúrgico en 1147 mujeres sometidas a cesárea, demostró una superioridad de la clorhexidina (riesgo relativo de 0,55; IC 95%, 0,34 to 0,90; P=0,02) 29 . -En general para la preparación antiséptica de la piel del sitio quirúrgico se recomienda el uso de una solución alcohólica (alcohol isopropílico al 70%) de GCH al 2%.…”
Section: B En La Sala De Cirugíaunclassified
“…The products made of povidone iodine are inactivated with the presence of organic material. -Cleansing the skin prior to antiseptic preparation for surgery was more effective in reducing the bacterial load than using only the antiseptic application 21,29 ). However, Lefebvre et al Performed a review and metaanalysis ( 7 studies with 1650 patients) in order to evaluate the advantage of applying a thorough cleansing prior to the application of the antiseptic solution with respect to SSI risk and found no differences (RR 1.02, 95% CI 0.82, 1.26).…”
Section: Recommendationsmentioning
confidence: 99%